2019
DOI: 10.7150/jca.31450
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of HPV integration in cervical intraepithelial cells

Abstract: Cervical cancer is one of the most common malignant tumors in gynecology. Deploying HIVID, a cost-effective technique to detect HPV integration sites, our team had studied the characteristics of HPV integrations in cervical exfoliated cells. Our results indicated that both the sample proportion and the number of HPV integrations gradually increased following the development of cervical lesion. Meanwhile, our data also revealed that there were recurrent genes integrated by HPV in cervical exfoliated cells. Coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 22 publications
4
13
0
4
Order By: Relevance
“…Our data indicated that most of the integration sites exist in the intergenic region of the human genome, concordant with previous studies ( Bodelon et al, 2016 ; Pinatti et al, 2017 ; Brant et al, 2018 ; Koneva et al, 2018 ; Li et al, 2019 ). Since human genome was identified with large portion (∼60%) of intergenic region, our results identified about 40% integration sites located in intergenic region of human genome, which showed no significant difference.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data indicated that most of the integration sites exist in the intergenic region of the human genome, concordant with previous studies ( Bodelon et al, 2016 ; Pinatti et al, 2017 ; Brant et al, 2018 ; Koneva et al, 2018 ; Li et al, 2019 ). Since human genome was identified with large portion (∼60%) of intergenic region, our results identified about 40% integration sites located in intergenic region of human genome, which showed no significant difference.…”
Section: Discussionsupporting
confidence: 93%
“…After enrichment of virus genomic material using this method, the fusion fragment of human and HPV sequence is isolated and further sequenced by NGS. Many studies have used this method to identify large amount of integration sites with good accuracy ( Chandrani et al, 2015 ; Liu et al, 2016a , b ; Li et al, 2018 , 2019 ). Although NGS is powerful for discovering HPV integration sites, the quality of the results relies on many factors including the probe capture efficiency, sequencing depth, and analysis method.…”
Section: Introductionmentioning
confidence: 99%
“…However, HPV-associated cancers contain integrated, episomal or episomal/integrated forms of HPV genome at variable number of copies [74,75]. In addition, it seems that integration events occur randomly in the host cell genome, even though specific hot spots have been reported in cervical exfoliated cells [76]. When integration is not detected in carcinomas, other mechanisms account for E6 and E7 overexpression [77][78][79].…”
Section: Hpv Role In Epithelial Tumorsmentioning
confidence: 99%
“…Most of the HPVint studies are focused on carcinomas [ 20 , 29 , 30 , 31 ] where clonal selection for tumor growth has already happened, and an integration event showed several non-PCR duplicates reads. In this study, nevertheless, we analyzed the viral integration in precancerous samples [ 16 , 21 , 47 ] where a new analysis strategy was designed that allows us to identify reads with evidence of the viral integration with presumably high sensitivity ( Figure 1 ). It was found that virtually all samples analyzed presented viral integration (96%) (except one sample of scarce mapped reads).…”
Section: Discussionmentioning
confidence: 99%